Marchiafava-Bignami and Alcohol Related Acute Polyneuropathy: The Cooccurrence of Two Rare Entities - Samine Boloursaz; Sirous Nekooei; Farrokh Seilanian Toosi; Hossein Rezaei-Dalouei; Behrooz Davachi; Sahar Kazemi; Bita Abbasi (Case Reports in Neurological Medicine)
Objectives. The aim of this article is to represent the first reported case with cooccurrence of two rare alcohol related complications. Case Report. We report a 38-year-old man with chronic alcoholism who presented with both cranial and peripheral nerve palsy. On MRI examination characteristic findings of Marchiafava-Bignami disease were recognized. Discussion. Marchiafava-Bignami disease (MBD) is a rare complication of long-term, heavy alcohol abuse that has characteristic MRI findings. Acute alcohol related polyneuropathy (AARP) is another rare and not-well-understood complication of chronic alcohol abuse. We could not find any previous report of the cooccurrence of these two complications in the literature.